Pure unlimited love : an eternal creative force and blessing taught by all religions - Templeton, John, 1912-2008 (Templeton Foundation Press, 2000)
Understanding and expressing unconditional love-also called agape love-can be a lifelong quest. First, however, we must ask ourselves and others what it is. Is it an action, a universal energy, or a creative principle? And if we understand it, can its expression ever be realized or is it simply a divine attribute? These and other questions are addressed in an inspirational and practical style in this philosophical essay from Sir John Templeton. He seeks to define pure, unlimited love as the ""transcendent power of divine love that expresses itself through our hearts and minds when we are open.